Persistence of persistent pulmonary hypertension of the newborn: A case of de novo TBX4 variant - Stephanie M. Tsoi; Kirk Jones; Elizabeth Colglazier; Claire Parker; Hythem Nawaytou; David Teitel; Jeffrey R. Fineman; Roberta L. Keller (Pulmonary Circulation, 2022)
Abstract We present a case of a late preterm infant placed on extracorporeal life support in the first day of life for persistent pulmonary hypertension of the newborn. Developmental arrest, pulmonary vascular hypertensive changes, and pulmonary interstitial glycogenosis were present on lung biopsy at 7 weeks of age. Pulmonary hypertension has persisted through childhood. Genetic testing at 8 years identified a novel mutation in TBX4.